A study of adverse maternal-foetal outcomes in nephrotic syndrome combined with preeclampsia - Dong Li; Minyi Zhang; Shuxiu Xu; Ziwei Bian; Xiaoli Huang; Guifang Hu; Jing Li (BMC, 2023)
Abstract Background Although the majority of pregnancies with preeclampsia are characterised by elevated blood pressure, preeclampsia is often associated with nephrotic syndrome with similar symptoms such as high proteinuria and bilateral lower limb oedema. In this study, we compared the maternal-foetal outcomes of pregnant women with preeclampsia in a population with nephrotic syndrome and explored the factors that contribute to the corresponding outcomes and disease development. Methods A total of 90 pregnant women were included in this study, of whom 30 had nephrotic syndrome and were diagnosed with preeclampsia during pregnancy, and 60 had nephrotic syndrome alone. Descriptive statistical analyses of baseline data were performed to analyse the effect of combined preeclampsia on maternal and foetal pregnancy outcomes using unadjusted and adjusted logistic regression models. Results In this study, the baseline data of the two study populations demonstrated no differences except for the history of caesarean section and 24-h proteinuria results, which were significantly different (P < 0.05). The risk of preterm birth in the nephrotic syndrome with preeclampsia group was 8.25 (95% CI:3.041-22.084 P < 0.05); for a low birth weight, the risk was 6.00 (95% CI:2.302-15.638 P < 0.05); for foetal distress,the risk was 5.667 (95% CI:2.070-15.514 P < 0.05); and the risk of foetal birth restriction was 7.429 (95% CI: 2.642-20.885 P < 0.05). A risk-based analysis of adverse maternal outcomes yielded a risk of miscarriage of 2.200 (95% CI: 0.584-8.291; P > 0.05). After adjusting the model for each outcome, significant risks of preterm labour, foetal birth restriction, and low birth weight were revealed (P < 0.05). Conclusion Combined preeclampsia has a significantly higher risk of adverse pregnancy outcomes for the foetus.Therefore, the prevention and control of eclampsia in pregnant women should be improved to ensure maternal and neonatal health.